2014
DOI: 10.1007/s11239-014-1091-4
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-eluting versus bare metal stents in primary PCI: a pooled patient-level meta-analysis of randomized trials

Abstract: Concerns have emerged regarding a higher risk of stent thrombosis after drug-eluting stent (DES) implantation, especially in the setting of ST-segment elevation myocardial infarction (STEMI). Therefore, we performed a meta-analysis based on individual patient data to evaluate long-term safety and effectiveness of paclitaxel-eluting stent (PES) as compared to bare metal stents (BMS) in patients undergoing primary percutaneous coronary intervention (PCI) for STEMI. We examined all completed randomized trials on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 43 publications
3
56
0
2
Order By: Relevance
“…Although PCI with DES improves efficacy outcomes in patients with STEMI, maintenance of superior safety outcomes in the long term has not yet been conclusively demonstrated in comparison to BMS in STEMI, even for newer-generation DES [5][6][7][8] . Late adverse events have been linked to an inflammatory reaction and delayed arterial healing -at least in part due to durable polymer coatings -and the extent of this problem may be more pronounced in the setting of STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…Although PCI with DES improves efficacy outcomes in patients with STEMI, maintenance of superior safety outcomes in the long term has not yet been conclusively demonstrated in comparison to BMS in STEMI, even for newer-generation DES [5][6][7][8] . Late adverse events have been linked to an inflammatory reaction and delayed arterial healing -at least in part due to durable polymer coatings -and the extent of this problem may be more pronounced in the setting of STEMI.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies [1][2][3][4][5][6][7] have shown that uncoated BMS placement is inferior to DES use in terms of reducing target lesion or vessel revascularization during a 1 to 3 year follow-up period after emergency stent implantation at the site of coronary occlusion. No significant difference was observed between BMS and DES in terms of the incidence of death and recurrent AMI [1,2,6,[10][11][12].…”
Section: Discussionmentioning
confidence: 99%
“…No significant difference was observed between BMS and DES in terms of the incidence of death and recurrent AMI [1,2,6,[10][11][12]. On the other hand, accumulating data began to show a higher risk of stent thrombosis in those treated with DES over a 1-year follow-up period [3,6,9]. Kalesan et al [8] demonstrated in meta-analysis that 1 year after AMI treatment, very late SO is significantly more likely to occur in patients receiving DES than in those with BMS placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,[5][6][7] Drug-eluting stents (DES) designed to directly address ISR have further reduced restenosis rates to less than 10% but are associated with an increased risk of late in-stent thrombosis, and the long-term effects after complete elution of the therapeutic agents remain unclear. [8][9][10] To further develop strategies to prevent ISR, continued elucidation of the pathobiologic processes underlying neointima formation following placement of BMS remains warranted.…”
Section: Introductionmentioning
confidence: 99%